Three-Input One-Output Voltage-Mode Universal Filter Using Simple OTAs - สุขใสบูลย์ พิชัย; นบนอบ บุญยิ่ง; คำเงิน มนตรี (Frontiers in Engineering Innovation Research, 2015)
This paper presents a three-input one-output voltage-mode electronically tunable universal filter using only simple CMOS operational transconductance amplifiers. The proposed filter provides lowpass, highpass, bandpass, bandstop and allpass filters into one single topology. For realize all the filtering functions, no component-matching conditions and no inverting-type input signals are required. The natural frequency and the quality factor can be controlled orthogonally and electronically by adjusting the bias currents. The proposed filter is simulated using PSPICE simulators to confirm the presented theory.